Pendekatan Statistika Dalam Analisis Keandalan Struktur Bangunan Gedung Terhadap Beban Gempa - Hia, Tafianus (CV. SINAR HOWUHOWU, 2026)
Buildings located in seismic-prone areas require a high level of structural reliability to ensure safety and adequate performance throughout their service life. Conventional approaches to seismic structural design are generally deterministic and do not fully represent the uncertainties inherent in material properties, structural parameters, and seismic loads. This study aims to examine the application of a statistical approach in the reliability analysis of building structures subjected to earthquake loads. The research method involves modeling a reinforced concrete building structure in which material properties and seismic loads are treated as random variables. Structural reliability analysis is conducted using the First Order Reliability Method (FORM) and validated through Monte Carlo simulation. The results indicate that the statistical approach provides a more comprehensive evaluation of structural safety by quantifying reliability indices and probabilities of failure. Overall, the structure satisfies the minimum reliability criteria; however, several critical elements exhibit relatively lower reliability levels. These findings highlight the importance of integrating probabilistic approaches into the design and evaluation of earthquake-resistant building structures, particularly in regions with high seismic activity.